ANALISIS PENGARUH KINERJA PELAYANAN DAN KEPUASAN KONSUMEN TERHADAP KECENDERUNGAN PEMBELIAN KEMBALI (REPURCHASE) (STUDI KASUS DI RUMAH MAKAN LAMUN OMBAK PADANG) - Patria Nagara; Dedi Mardianto; Yelda Desmita (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2019)
Lamun Ombak restaurant is a business that has a big name in the city of Padan today, in the city of Padang also many emerging big names that also have similar businesses, such as restaurants Lubuk Idai, restaurant Pauh, Simple restaurant that continues to expand market in various areas in Padang City. To address the increasingly competitive competition, Lamun Ombak restaurants must still maintain excellent service and customer satisfaction to maintain customer loyalty. This study aims to determine the Influence Analysis of Service Performance and Consumer Satisfaction Against Repurchase Trend (Case Study at Lamun Ombak Restaurant Padang). The independent variables are Service Performance (x1) and Consumer Satisfaction (x2). The dependent variable is the Buying Trend (Y). The sample in this research is 100 consumers who come to visit. Data were collected using documentation and interviews. Hypothesis testing using analysis, regression, t test, F test and determination. The results showed partially and simultaneously service performance and customer satisfaction have a significant effect on the trend of repurchase in the Lamun Ombak restaurant with a significance value of 0.000. While viewed from the coefficient of determination obtained R square value of 0.443 has the meaning that the ability of independent variables to explain the amount of variation in the dependent variable is 44.3% the rest explained other variables that are not included in the equation.